The effects of root-zone temperature and limestone on root-zone medium pH and electrical conductivity on New Guinea impatiens 'Celebration Orange' - Welles, Melanie L., author; Newman, Steven E., advisor; Hartley, David E., committee member; Brick, Mark A., committee member; Miller, Robert O., committee member (Colorado State University. Libraries, 2013)
The purpose of this experiment was to examine the effects of various media temperatures and pH on nutrient availability for New Guinea impatiens (Impatiens x hawkeri Bull.). It is important for greenhouse growers to be cognizant of the root-zone medium pH, as New Guinea impatiens are sensitive to nutrient toxicities at low pH. It is thought that limestone at low root-zone medium temperatures is not quickly activated leading to these toxicities. The objectives of this project were to determine: The effect of root-zone medium pH on foliar symptoms of iron and manganese toxicity; and the effect rates and grind size of limestone have on root-zone medium pH. Various rates of limestone and different grind sizes were incorporated into a sphagnum peat moss-based medium at set temperatures. This experiment used a two-way thermogradient plate to maintain nine varying, but stable root-zone medium temperatures. Plant growth as well as root-zone medium pH was monitored. Changes in root-zone medium pH were monitored over time. The goal of this research was to provide New Guinea impatiens growers with information on root-zone media interactions so as to produce a more saleable product with lower energy input. A few of the 'Celebration Orange' New Guinea impatiens grown for the studies expressed foliar symptoms of marginal chlorosis, but not at the level that was expected. Without any limestone added to the root-zone medium the pH was too low. At the 3 kg/m3 rate of limestone incorporation the pH ranged from 6.2 to 7.15 over all the root-zone medium temperatures. The 6 kg/m3 incorporation rate was too high; the lowest pH was 6.73, which is above the desired pH range. The smallest calcitic limestone grind sizes of 45 and 75-150 μìm grind size did raise the pH faster than the 250-1,200 μm grind size. Both the 45 μm and the 75-150 μm grind sizes of limestone incorporated preplant at the rate of 3 kg/m3 did have some root-zone medium pH readings that fell within the target pH range.